Relokasi Gempa Utama dan Susulan Mentawai 7,8Mw dan Implikasinya terhadap Seismotektonik Sumatra: Arya Dwi Candra, Bagus Jaya Santosa - Arya Dwi Candra, Arya Dwi Candra; Bagus Jaya Santosa, Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2025)
Sumatra is one of the islands that has high tectonic activity which is caused by tectonic zones around it. Mentawai fault is one of the tectonic zones that often leads to strong seismic activity. One of them was October 25, 2010 Mentawai earthquake that rocked Sumatra with 7,8Mw strength. This study used HYPO71 program to improve the accuracy of hypocenter position. The data used in this study are a mainshock and aftershocks earthquake data that occurred on October 25, 2010. Seismogram recorded in three components from earthquake events analyzed, they are the two horizontal components (-E, -N) and a vertical component (-Z) from seismic obeservation station around the hypocenter. Process of raw data preparation includes instrument correction, rotating into radial and transverse coordinates and time alignment of the earthquake origin time. Arrival time data of P and S wave from seismograms picking results used as input to the HYPO71 program. The result of the earthquake relocation using HYPO71 shows that the location of the hypocenters havemore focus distribution than the hypocenter distribution prior to relocation. It may explain the absence of coherence between aftershock hypocentersposition with geological conditions of megathrust and Mentawai fault. Aftershocks that occurred may be due to the rupture in the Mentawai fault which was triggered by a mainshock.